2018
DOI: 10.1080/21691401.2018.1511575
|View full text |Cite
|
Sign up to set email alerts
|

Oral insulin delivery by carboxymethyl-β-cyclodextrin-grafted chitosan nanoparticles for improving diabetic treatment

Abstract: In this paper, a new oral insulin formulation, insulin-loaded carboxymethyl-b-cyclodextrin-grafted chitosan nanoparticles (insulin/CMCD-g-CS NPs), was fabricated by ionic crosslinking technique. The therapeutic efficacy of new formulation was investigated in detail. Firstly, the CMCD-g-CS was synthesized by EDC-mediated esterification reaction. The prepared CMCD-g-CS exhibited favourable loading capacity and encapsulation efficiency of drug. The release experiment in vitro showed that the nanocarrier could eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 33 publications
(41 reference statements)
0
13
0
1
Order By: Relevance
“…When the medium was changed from pH 2.0 to pH 6.8 (simulated intestinal fluid, SIF), due to the pH sensitivity of AC‐NPs, the drug release rate significantly increased to about 48.3% within 2 h. In the following 8 h, the release slowly increased to 70.9%, which may be caused by the swelling and dissolution of alginate nanoparticles in PBS buffer. Previous studies have also confirmed that insulin release was delayed under simulated gastric fluid and showed significant release at pH 6.8 of simulated intestinal fluid 34–36 …”
Section: Resultsmentioning
confidence: 71%
“…When the medium was changed from pH 2.0 to pH 6.8 (simulated intestinal fluid, SIF), due to the pH sensitivity of AC‐NPs, the drug release rate significantly increased to about 48.3% within 2 h. In the following 8 h, the release slowly increased to 70.9%, which may be caused by the swelling and dissolution of alginate nanoparticles in PBS buffer. Previous studies have also confirmed that insulin release was delayed under simulated gastric fluid and showed significant release at pH 6.8 of simulated intestinal fluid 34–36 …”
Section: Resultsmentioning
confidence: 71%
“…In diabetic disease, for a better function of oral insulin administration, Song et al, in 2018, fabricated carboxymethyl-β-cyclodextrin-grafted chitosan nanoparticles (insulin-CMCD-g-CS NPs) via the ionic crosslinking method. The result of the study demonstrated that the oral administration of insulin-loaded CMC-g-CS nanoparticles declined the level of blood sugar in the mice model [ 152 ]. In addition, CD-NSs were proposed as insulin carriers too [ 153 ].…”
Section: Cyclodextrin Monomers and Polymers As An Enhancer Of The Drug Effectmentioning
confidence: 99%
“…Chitosan and CD were integrated together to prepare carboxymethyl-β-CD-grafted CS nanoparticles (CMCD-g-CS nanoparticles) via ionic gelation method [ 113 , 115 ]. Song et al, have synthesised CMCD-g-CS by EDC-mediated esterification reaction, then TPP solution was gradually added into the insulin/CMCDg-CS solution for 1 h under continuous stirring.…”
Section: Chitosan Modificationmentioning
confidence: 99%
“…A greater extent and higher insulin released was attainable in SIF with a cumulative amount higher than 80% over 1.5 h dissolution, achieving bioavailability of 14.54%. Insulin-CMCD-g-CS nanoparticles were advocated to be highly biocompatible with minimised cellular toxicity effects, where more than 80% cell viability has reported after incubating in nanoparticles solution at a concentration range of 20–120 µg/mL [ 115 ].…”
Section: Chitosan Modificationmentioning
confidence: 99%